Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2025)
Table of Content:1. Factors Influencing Mathematics Achievement among Saudi Students Compared to High-Performing Countries in TIMSSDr. Mohammed Humaydan Alhisony, Prof. Mohammed Sant Alharbi2. A teaching program based on the Authentic Instruction approach and its effectiveness  in developing health awareness and future thinking skills among second-grade students in scienceDr. Maryam Abdu Kariri, Prof. Hanan Abdul-Rahman Al-Arini3. The effect of challenge-based learning on developing algebraic thinking skills  among third-year middle school female studentsMs. Lulwah Abdullah Al-Fahd, Co-Prof. Khaled Mohammed Al-Sharif4. A Proposed Concept for a Teaching Strategy Based on the Schwartz Model to Develop Syntactic (Nahwi) Thinking Skills Among Secondary School Female StudentsMs. Khadijah Atiah Falih Al-Huzali5. Assessment for Learning Practices among Outstanding Science Teachers during the COVID-19 Pandemic: A Case Study in the Sultanate of OmanMs. Sajda Ahmad Abdullah Al-Khaburi, Dr. Huda Ali Said Al-Hosni6. Evaluating the Current State of the Life and Family Skills Curriculum for Third-Grade Intermediate Students in Light of Constructivist Theory PrinciplesMs. Nada Abdel-Aziz Al-Maashouq , Co-Prof. Manal Abdel-Rahman Al-Shabl7. Content analysis of the human body systems course for the third secondary grade in light of creative thinking skillsMs. Haya Abdulaziz Nasser Bin Ghaith8. The effectiveness of the Frayer Model in teaching grammar concepts to middle school studentsMr. Firas Ahmad Shawakh
Keywords: Journal of Curriculum and Teaching Methodology